Sistema de controle de pose para uma cadeira de rodas inteligente - Alves, Tiago Giacomelli (2018)
In order to improve the comfort of power wheelchair users, it is proposed in this dissertation the implementation of a position and orientation control system which allow the users to travel the desired trajectories safely, without the need for constant interaction with the device command system. To reach this objective, it is proposed a methodology for the implementation of a control system, able to drive the vehicle from an initial position to the desired one or make it follow a specified trajectory, from commands received in the system. The proposed control system is based on a cascade control law, composed by a nonlinear pose controller and a velocity tracking controller. Two velocity control strategies are proposed. The first one uses a velocity controller composed of two joint-independent Proportional-Integral controllers while the second one uses a velocity controller based on the dynamic model, which is linearized by a state-feedback. The methods are implemented using the ros_control package, provided by the framework Robot Operating System (ROS). The evaluation of the proposed methods is done with a differential-drive mobile robot, which has the same kinematic configuration as the majority of commercial power wheelchairs. The results of dynamic-model parameter identification, as well as the convergence of the controlled variables by using the proposed control methods, are presented. The results demonstrate that the methods achieve the proposed control objectives.